CUSTOMS AND TRADITIONS OF THE TURAN PEOPLES IN CHINESE SOURCES (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This article analyses the information about the history, customs and legal system of the peoples of Turan contained in ancient Chinese written sources. The records about the peoples of Turan in the official works of Chinese chronicles ‘Twenty-four Histories’ (二十四史) are investigated. In particular, the origin of the Kyrgyz, their relations with China and the Turkic Kaganate, as well as details of customary law - the system of ‘Tөre.’ are considered.’ The article also analyses Chinese historians' ideas about social life and the system of governance of the Turkic peoples, revealing the role of such values as justice, honesty, obedience and reward in Turkic society. The article is an important study in the study of the history of Turkic legal and political traditions.